MEASURED AND CALCULATED INTEGRAL REACTIVITY OF CONTROL RODS IN RSG-GAS FIRST CORE - Wahid Luthfi; Surian Pinem; Donny Hartanto; Lily Suparlina; Dwi Haryanto (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
The control rod worth is one of the important parameters for the operation of a nuclear reactor. Proper measurement and calculation of the control rod worth are essential for the safe reactor operation under normal and transient conditions that are initiated by a postulated event such as a stuck rod, control rods ejection, etc. This paper presents calculation results of integral reactivity of the RSG-GAS research reactor first core and its comparison with the experimental data. Calculations were performed using the continuous energy transport code Serpent 2 with ENDF/B-VIII.0 nuclear data. Integral reactivity measurement was done by compensating method with control rod bank, regulating rod, and reactivity meter. Calculations are carried out for each method used in control rod measurement data with an aim to validate calculated results to experimental data. Compared with the measured experiment data, there are no significant differences in calculation results of integral reactivity. The maximum difference of the control rod's total reactivity is 1.26% compared to the measurement carried out by compensating method with regulating rod.